Updates on Physical Fitness in Children (IntechOpen, 2024)
Updates on Physical Fitness in Children is a comprehensive compilation shedding light on vital aspects of children's physical health and well-being. Spanning five insightful chapters, this book delves into the intricate relationship between physical fitness, body composition, cognitive skills, and the crucial role of physical activity in a child's life. From exploring the impact of growth on fitness to practical strategies for incorporating physical activities into daily routines, each chapter offers valuable insights backed by empirical research. Furthermore, it addresses the challenges of measuring cardiorespiratory fitness in low- and middle-income settings, providing practical solutions for effective assessment. Moreover, including motor games aimed at nurturing fundamental motor skills adds a suitable dimension to the discussion, making this volume a valuable resource for educators, healthcare professionals, and parents. With its interdisciplinary approach and practical recommendations, Updates on Physical Fitness in Children is an indispensable guide for promoting the holistic well-being of the younger generation, fostering healthier lifestyles and brighter futures.